ISBAR Communication Implementation in Nursing Handover: A Sequential Explanatory Mixed Method Study at Pariaman Hospital - Husna, Novriani; Rahman, Waldi (LPPM Universitas Prima Nusantara Bukittinggi, 2026)
Effective communication during nursing handovers is fundamental to patient safety and care continuity, yet standardized protocols remain underutilized in Indonesian regional hospitals. This study examined ISBAR (Identify, Situation, Background, Assessment, Recommendation) communication implementation in nursing handover processes at Pariaman Hospital, West Sumatra. A sequential explanatory mixed-method design was employed because quantitative measurement alone cannot explain the contextual mechanisms, nurses' lived experiences, and organizational dynamics that determine implementation success or failure; the qualitative strand was therefore necessary to contextualize and explain numerical findings. Quantitative data were collected from 35 implementing nurses using a validated 25-item questionnaire adapted from the ISBAR Communication Assessment Tool, followed by semi-structured interviews with nine purposively selected informants. Quantitative analysis utilized SPSS version 26.0 for descriptive statistics and Spearman correlation tests, while qualitative data underwent Braun and Clarke's thematic analysis framework. Findings revealed moderately effective implementation overall (mean=3.61), with practical implementation highest (mean=3.78) and handover quality lowest (mean=3.45). Strong correlations emerged between knowledge-implementation (r=0.612), attitude-implementation (r=0.548), and implementation-quality (r=0.689). Qualitative analysis identified management support (88.9%), practical tools (77.8%), and continuous training (66.7%) as key facilitators, while time constraints (66.7%), senior nurse resistance (44.4%), and documentation system gaps (44.4%) hindered implementation. A critical knowledge-practice gap existed particularly under high-workload conditions. The study proposes a four-phase implementation model addressing identified barriers through preparation, graduated rollout, continuous evaluation, and organizational integration to optimize handover quality in resource-constrained settings.